Oxidative stress parameters and inflammatory and immune mediators as markers of the severity of sepsis - Bavunoglu, Isil; Genc, Habibe; Konukoglu, Dildar; Cicekci, Hayriye; Sozer, Volkan; Gelisgen, Remise; Uzun, Hafize (J INFECTION DEVELOPING COUNTRIES, 2016)
Introduction: Sepsis is a complex inflammatory syndrome with diverse etiology and wide spectrum of severity. The aim of this study was to investigate whether inflammatory mediators, in comparison with oxidative parameters, are associated with severity of sepsis. Methodology: Plasma neopterin, adenosine deaminase (ADA), vascular cell adhesion molecule (VCAM), intracellular adhesion molecule (ICAM), interleukin (IL)-1, IL-6, and tumor necrosis factor alpha (TNF-alpha), as inflammatory mediators, and serum nitric oxide (NOx), nitrotyrosine (NT), oxidized LDL (oxLDL) levels, serum paraoxonase 1 (PON1) activity, and erythrocyte glutathione (GSH) levels as oxidative stress parameters of 12 patients with mild sepsis, 25 patients with severe sepsis, and 20 healthy control subjects were evaluated. NOx, GSH levels and PON1 activity were determined by colorimetric methods, whereas neopterin, VCAM, ICAM, IL-1, IL-6, TNF-alpha, NT, and oxLDL levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: All parameters in mild and severe sepsis were significantly different from those of healthy subjects, except ADA activities. Patients with severe sepsis exhibited higher IL-6, TNF-alpha, NT, and oxLDL levels than patients with mild sepsis. GSH (98%, 98%), oxLDL (98%, 98%), VCAM-1 (99%, 99%), and ICAM-1 (99%, 99%) have much more sensitivitiy and specificity in sepsis. Conclusions: Our results suggest that the oxidative stress and inflammatory response in patients with sepsis were increased and that serum IL6, TNF-alpha, NT, and oxLDL levels were correlated with the severity of sepsis. Therefore, increases in these parameters may contribute to the dysfunction or failure of one or more organs, or even death, in sepsis.
Keywords: Sepsis; cytokine; nitrotyrosine; glutathione; nitric oxide; CRITICALLY-ILL PATIENTS; TUMOR NECROSIS FACTOR; SEPTIC SHOCK; ORGAN FAILURE; DISEASE; INJURY; MODEL; Infectious Diseases